2022
DOI: 10.1186/s13018-021-02896-3
|View full text |Cite
|
Sign up to set email alerts
|

Early results of fixed-bearing unicompartmental knee replacement designed for the lateral compartment

Abstract: Background Isolated lateral compartment knee arthritis is less prevalent than medial. While the reported results of medial unicompartmental knee replacement (UKR) have been good and comparable to total knee replacement, the results of lateral UKR have been mixed. We present the short-term results and survivorship of a fixed-bearing UKR designed specifically for the lateral compartment. Methods We report the result of 130 primary fixed-bearing later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
4
9
1
Order By: Relevance
“…The dislocation rate of 10% is noticeable higher than in previous reports, even if all surgeries were performed by well-experienced senior surgeons who were familiar with the modified surgical technique [41,42]. In contrast, survivorship of FB-UKR for the endpoint "revision for any reason" was significantly higher with 98.3% at 2.7 years than for MB-UKR and is in line with other recent studies of lateral FB-UKR [3,35].…”
Section: Discussionsupporting
confidence: 85%
“…The dislocation rate of 10% is noticeable higher than in previous reports, even if all surgeries were performed by well-experienced senior surgeons who were familiar with the modified surgical technique [41,42]. In contrast, survivorship of FB-UKR for the endpoint "revision for any reason" was significantly higher with 98.3% at 2.7 years than for MB-UKR and is in line with other recent studies of lateral FB-UKR [3,35].…”
Section: Discussionsupporting
confidence: 85%
“…We demonstrate excellent clinical results with a high mean OKS of 39.9 and 81.1% of our patients having a good to excellent outcome according to the OKS criteria. Comparable results have been reported for patients following lateral FB-UKR [ 37 , 38 ] and lateral MB-UKR [ 39 , 40 ]. The mean postoperative ROM of 136° in our cohort appears to be higher than those of earlier reports of patients following lateral UKR [ 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 62%
“…Two thousand one hundred and sixty studies were then screened for eligibility based on their titles and abstracts. After a screening and retrieval process, 40 articles received a full‐text evaluation for eligibility and finally, 26 studies 7–9,15–37 were included in this meta‐analysis. Detailed information regarding study selection is displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Refinements in patient selection criteria, surgical technique as well as instrumentation, and implant design aimed at better accommodating the lateral compartment, have greatly contributed to the increase in implant survivorships during this period. 8,16,19,20,22,28,32,37 It is therefore likely that the exclusion of a study 21 published in 1996 could reduce heterogeneity and improve the 10-year survival in our sensitivity analysis. Surprisingly, we further stratified studies into two subgroups according to the publication year of 2015 and found significantly lower survivorships at longer-term follow-up (15-20 years) among recently published studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation